2016
DOI: 10.1145/2753767
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Interactions and Performance: Predicting Team Performance from Thin Slices of Conflict

Abstract: Do teams show stable conflict interaction patterns that predict their performance hours, weeks, or even months in advance? Two studies demonstrate that two of the same patterns of emotional interaction dynamics that distinguish functional from dysfunctional marriages also distinguish high from low-performance design teams in the field, up to 6 months in advance, with up to 91% accuracy, and based on just 15minutes of interaction data: Group Affective Balance, the balance of positive to negative affect during a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 91 publications
0
11
0
1
Order By: Relevance
“…Similarly, in a study by Lambert et al (2014) raters could accurately identify which partner in a couple cheated on the other by watching 3-to 5-min clips of the couple's interactions. Jung (2016) also provides evidence that a team's work performance could be predicted by thin slice ratings of the quality of interactions between different team members based on 15 min of observation.…”
Section: The Thin Slices Procedures In the Context Of Instructional Rementioning
confidence: 95%
“…Similarly, in a study by Lambert et al (2014) raters could accurately identify which partner in a couple cheated on the other by watching 3-to 5-min clips of the couple's interactions. Jung (2016) also provides evidence that a team's work performance could be predicted by thin slice ratings of the quality of interactions between different team members based on 15 min of observation.…”
Section: The Thin Slices Procedures In the Context Of Instructional Rementioning
confidence: 95%
“…Perspective: Affective processes are a crucial in determining team performance. Through our work we found that how emotions were expressed and regulated over time during short episodes of a team's interaction predicted subjective as well as objective outcomes of teamwork weeks [] and even months ahead [7]. We currently don't know what impact robots have on these affective team processes.…”
Section: Jodi Forlizzi (Design)mentioning
confidence: 98%
“…Not having colocated teams makes collaboration, role identification, and trust difficult; moreover, the progressive trends of globalization and specialization in the construction industry make collaboration between design stakeholders in distant locations crucial [59]. This latter point has generated great interest in the study of team dynamics and emotions [60] and mental models [61] to integrate and coordinate design teams in the construction industry.…”
Section: Design Teams In the Construction Industry-cluster 2 (Green)mentioning
confidence: 99%